OCCURRENCE OF ZOONOTIC CAMPYLOBACTER IN CHILDREN - M.Dhanalakshmi; M.Sekar; L. Gunaseelan; V.Bhanu Rekha (Indian Journal of Veterinary and Animal Sciences Research, 2024)
Campylobacter is the commonest reported bacterial cause of infectious intestinal disease. To study the epidemiology of Campylobacter infection among children, 100 stool samples along with patients anamnesis were collected from the clinical diarrheic reported to Enterology unit of Institute for child Health and centre for Children, Egmore, Chennai, Tamil Nadu between May 2013 to June 2013. Samples were subjected to traditional culture and modern PCR techniques, both of which revealed same results of 13% prevalence of Campylobacter sps (8% C.jejuni & 5% C.coli). Analyzing the patients anamnesis to study the epidemiological determinants, sex has a significance (P<0.05). Age and residential area have no significance and summer season and cross contamination could be probable determinants for the infection.